Analysis Of Determinant Factors Affecting The Leadership Style Of Chief Of Room In The Inpatient Room At Royal Prima Medan General Hospital - Ryeo Ramadhan Chairun; Marlinang Isabela Silalahi; Sri Lestari Nasution (International Journal of Health and Pharmaceutical (IJHP), 2024)
The head of the room is managing all the resources in the care unit to produce quality services. The head of the room is responsible for carrying out the supervision of nursing services to patients in the treatment room he leads. The head nurse of the room is responsible for leading and organizing the activities of servants and nursing care. The role of nurse leadership style has a large influence on nurses' work motivation. This is because the leadership of a good head nurse room will increase nurse job satisfaction, so that if leadership is not good it will reduce the level of nurse job satisfaction. Some previous studies suggested that leadership is one of the main factors that influence performance because leadership is the driving force for all resources within an organization. In leadership itself there are several parts of leadership that affect performance such as leadership style, leadership traits, type of leadership, work motivation, empowerment, work environment, organizational culture, leadership quality, and organizational commitment Research conducted aims to determine the analysis of influence factors leadership style on the performance of nurses in class 3 inpatient rooms Royal Prima Hospital in 2022. This research is a type of quantitative research with a cross sectional approach. The sample in the study was 110 room nurses. Data collection techniques in research using questionnaires. The results of this study found a significant relationship between communication factors (p = 0.001), planning (p = 0,000), direction (p = 0,000), and work discipline (p = 0,002) with the performance of nurses in class 3 Royal Prima Hosptal inpatient care. The conclusion of this study is that of the four variables studied, there was one of the most dominant variables influencing nurses' work motivation in class 3 inpatient rooms of Royal Prima Hospital in 2022, namely directing work by the head of the room.